Blunt Traumatic Aortic Injury in the Pan‐scan Era. (30th December 2019) - Yu, Louis; Baumann, Brigitte M.; Raja, Ali S.; Mower, William R.; Langdorf, Mark I.; Medak, Anthony J.; Anglin, Deirdre R.; Hendey, Gregory W.; Nishijima, Daniel; Rodriguez, Robert M.
Abstract: Background: In the era of frequent head‐to‐pelvis computed tomography (CT) for adult blunt trauma evaluation, we sought to update teachings regarding aortic injury by determining 1) the incidence of aortic injury; 2) the proportion of patients with isolated aortic injury (without other concomitant thoracic injury); 3) the clinical implications of aortic injury (hospital mortality, length of stay [LOS], and rate of surgical interventions); and 4) the screening value of traditional risk factors/markers (such as high‐energy mechanism and widened mediastinum on chest x‐ray [CXR]) for aortic injury, compared to newer criteria from the recently developed NEXUS Chest CT decision instrument (DI). Methods: We conducted a preplanned analysis of patients prospectively enrolled in the NEXUS Chest studies at 10 Level I trauma centers with the following inclusion criteria: age > 14 years, blunt trauma within 6 hours of ED presentation, and receiving chest imaging during ED trauma evaluation. Results: Of 24, 010 enrolled subjects, 42 (0.17%, 95% confidence interval [CI] = 0.13% to 0.24%) had aortic injury. Most patients (79%, 95% CI = 64% to 88%) had an associated thoracic injury, with rib fractures, pneumothorax/hemothorax, and pulmonary contusion occurring most frequently. Compared to patients without aortic injury this cohort had similar mortality (9.5%, 95% CI = 3.8% to 22.1% vs. 5.8%, 95% CI = 5.4% to 6.3%), longer median hospital LOS (11 days vs. 3 days, p < 0.01), and higher median Injury Severity Score (29 vs. 5, p < 0.001). High‐energy mechanism and widened mediastinum on CXR had low sensitivity for aortic injury (76% [95% CI = 62% to 87%] and 33% [95% CI = 21% to 49%], respectively), compared to the NEXUS Chest CT DI (sensitivity 100% [95% CI = 92% to 100%]). Conclusions: Aortic injury is rare in adult ED blunt trauma patients who survive to receive imaging. Most ED aortic injury patients have associated thoracic injuries and survive to hospital discharge. Widened mediastinum on CXR and high‐energy mechanism have relatively low screening sensitivity for aortic injury, but the NEXUS Chest DI detected all cases.